Sonographic Detection of Pseudoaneurysm in Vascular Injury in Emergency Department - Chien, Li-Jen (Sultan Qaboos University Medical Journal, College of Medicine & Health Sciences, 2013)
A 31-year-old man suffered from a stab wound to the lower extremity. The patient had a hard sign of a vascular injury (a diminished distal pulse) and therefore probably should have undergone operative repair, but refused. One week later, he returned to our emergency department with a painful right thigh swelling. Bedside sonography was used to detect a pseudoaneurysm. Emergency sonography is a fast, non-invasive, and rapid decision-making approach in emergency practice.